Ongoing objectification, marginalization and sexualization of women in Michael Ondaatje’s The English patient and Divisadero - Burcar, Lilijana (ELOPE (Ljubljana), 2023)
The year 2023 marks Michael ondaatje’s 80th birthday, a landmark in the author’s life and an occasion for literary critics to look back and revisit what are perhaps some of the more troubling aspects of his literary production. ondaatje’s poetry and fiction have received little attention from feminist literary critics, which is due to the author’s conservative take on the figuration of female characters and representation of women. While some critics have proposed that The English Patient (1992), and therefore also by extension his novel Divisadero(2007), might signify a turning point in ondaatje’s otherwise problematic gender politics, this article demonstrates that earlier patterns of women’s objectification, sexualization and marginalization found in ondaatje’s poetry and fiction persist in both of these seemingly more progressive works, albeit in new forms and disguises. This article also introduces a new concept to the field of (feminist) literary theory, the so-called blazon in prose.
Keywords: Canadian literature; feminism; feminizem; kanadska književnost; Ondaatje, Michael